Massive Left Atrial Thrombus in Two Patients with Heparin-Induced Thrombocytopenia Type II after Cardiac Surgery - Mandryk, Yuriy; Czesla, Markus; Mogilansky, Christian; Stefkova, Kristina; Drees, Aloys; Massoudy, Parwis (TH Open, 2018)
Heparin-induced thrombocytopenia type II (HIT type II) can have devastating consequences in cardiac surgical patients. We report two cases of massive left atrial thrombus after mitral valve replacement and endocardial cryoablation in patients with HIT type II.
Keywords: heparin-induced thrombocytopenia; argatroban; mitral valve replacement; endocardial cryoablation